VC an American history - Nicholas, Tom (Associate professor) (Harvard University Press, 2019)
VC tells the riveting story of how the venture capital industry arose from the United States' long-running orientation toward entrepreneurship. From nineteenth-century whaling to the multitude of firms pursuing entrepreneurial finance today, venture capital has been driven by the pull of low-probability but substantial financial rewards. Appreciating the history of venture capital, Tom Nicholas shows, is essential to understanding the industry's future directions and possibilities, its challenges and prospects for surmounting them, and its place in America's exceptional style of capitalism.--